1997
DOI: 10.1016/s0378-1097(97)00393-5
|View full text |Cite
|
Sign up to set email alerts
|

Blue and yellow laccases of ligninolytic fungi

Abstract: Extracellular laccases from submerged cultures of Coriolus versicolor BKM F-116, Panus tigrinus 8/18, Phlebia radiata 79 (ATCC 64658), Phlebia tremellosa 77-51 and from cultures of Pa. tigrinus 8/18, Ph. radiata 79 and Agaricus bisporus D-649 grown on wheat straw (solid-state fermentation) were purified. All enzymes from submerged cultures had a blue colour and characteristic absorption and EPR spectra. Laccases from the solid-state cultures were yellow-brown and had no typical blue oxidase spectra and also sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(32 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…They can oxidate a variety of phenolic and inorganic compounds, including diphenols, polyphenols, and substituted phenols, using molecular oxygen as the electron acceptor [1, 2]. Although they were first reported and named from plant, laccases are widely distributed in higher plants and fungi and have also been found in insects and bacteria [3].…”
Section: Introductionmentioning
confidence: 99%
“…They can oxidate a variety of phenolic and inorganic compounds, including diphenols, polyphenols, and substituted phenols, using molecular oxygen as the electron acceptor [1, 2]. Although they were first reported and named from plant, laccases are widely distributed in higher plants and fungi and have also been found in insects and bacteria [3].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it has a yellow colour. It has already been reported in the literature that some fungal strains, which secrete blue laccase in submerged liquid cultures, secrete blue laccases when grown in solid-state fermentation containing natural lignin substrate, wheat straw [19]. The yellow laccases lack absorption band around 610 nm observed in cases of blue laccases.…”
Section: Resultsmentioning
confidence: 96%
“…The authors could not detect the blue absorption band around 610 nm in the purified laccase spectrum, indicating that it is a yellow laccase. It has also been reported that yellow laccases which oxidize non-phenolic substrates without the presence of electron transfer mediators [19,20] which are essential for the oxidation of non-phenolic substrates by blue laccases. The purified laccase was tested for its property of the oxidation of veratryl alcohol, a non-phenolic substrate which is not oxidized by blue laccases in the absence of the mediator molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing interest in their use to treat textile wastewaters which also contain auxiliary chemicals such as surfactants and salts [84,85]. Environmental pollutants (dioxins, polycyclic aromatic hydrocarbons, chlorophenols) which are some of the substrates of laccases, are not water soluble so the use of microemulsions was unavoidable [86].…”
Section: Laccasesmentioning
confidence: 99%